Laparoscopic Inguinal Hernia Repair in Children with Transperitoneal Division of the Hernia Sac and Proximal Purse String Closure of Peritoneum: Our Modified New Approach - Wheeler, A. A.; Matz, S. T.; Schmidt, S.; Pimpalwar, A. (European Journal of Pediatric Surgery, 2011)
To describe our results of laparoscopic transperitoneal division of the hernia sac with purse string closure of the proximal peritoneum for inguinal hernia repair in children.A retrospective case review of all patients undergoing laparoscopic herniorrhaphy with herniotomy by a single surgeon between January and August 2007 was performed evaluating perioperative and postoperative outcomes.A complete intracorporeal laparoscopic technique was utilized to inspect bilateral inguinal canals followed by circumferential division of the peritoneum at the deep ring (patent processus vaginalis) followed by purse string closure of the proximal peritoneum.31 inguinal hernias were repaired laparoscopically in 26 patients (23 boys, 3 girls). Median age was 36 months (range 1–168 months). 22 children had unilateral inguinal hernia repairs including 2 recurrent hernias; 4 children underwent repair of bilateral inguinal hernias. Mean operating time for unilateral and bilateral inguinal hernia repairs were 48.5±14 min and 61±13.8 min, respectively. 2 patients with a preoperative unilateral inguinal hernia were found to have bilateral inguinal hernias upon laparoscopic examination which were repaired. Postoperative pain was minimal in 20 (77%) patients at discharge. Mean telephone follow-up at 8±9.6 months demonstrated no recurrences to date.Laparoscopic inguinal hernia repair with transperitoneal division of the hernia sac and purse string closure of the proximal peritoneum allows for a minimally invasive option for pediatric inguinal hernia repair that mimics open inguinal hernia repair. At medium term follow-up there have been no recurrences to date, high parent satisfaction, minimal scarring and good cosmetic results.
Keywords: inguinal hernia; pediatric hernia; laparoscopic inguinal hernia repair; children hernia; laparoscopy